2017
DOI: 10.1155/2017/2676403
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Liver Granuloma/Abscess and Constrictive Aspergillosis Pericarditis with Central Nervous System Involvement: Different Remarkable Phenotypes in Different Chronic Granulomatous Disease Genotypes

Abstract: Chronic granulomatous disease (CGD) is a primary immune deficiency causing predisposition to infections with specific microorganisms, Aspergillus species and Staphylococcus aureus being the most common ones. A 16-year-old boy with a mutation in CYBB gene coding gp91phox protein (X-linked disease) developed a liver abscess due to Staphylococcus aureus. In addition to medical therapy, surgical treatment was necessary for the management of the disease. A 30-month-old girl with an autosomal recessive form of chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…Assessment of patient population characteristics in our study revealed that CPA was more likely to occur in patients with COPD, other chronic lung diseases and in patients with a history of corticosteroid usage, which was consistent with previously published studies (De Pauw et al, 2008; Eren Akarcan et al, 2017; Garth and Steele, 2017). At first, we measured Aspergillus -specific antibody levels in the CPA, non-CPA and healthy control patients, and discovered that levels of both As-IgG and As-IgM were in the lower limit in healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…Assessment of patient population characteristics in our study revealed that CPA was more likely to occur in patients with COPD, other chronic lung diseases and in patients with a history of corticosteroid usage, which was consistent with previously published studies (De Pauw et al, 2008; Eren Akarcan et al, 2017; Garth and Steele, 2017). At first, we measured Aspergillus -specific antibody levels in the CPA, non-CPA and healthy control patients, and discovered that levels of both As-IgG and As-IgM were in the lower limit in healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…We measured PTX3 in BALF and plasma in 431 patients initially suspected of having pulmonary aspergillosis. The morbidity of COPD and bronchiectasis in aspergillosis was significantly greater than in non-aspergillosis, and more patients in the aspergillosis group had a history of corticosteroid use, which was consistent with the findings of previous studies [18,19]. BALF and plasma PTX3 levels in aspergillosis subjects were greater than for the nonaspergillosis groups.…”
Section: Discussionsupporting
confidence: 90%
“…After dividing the aspergillosis group into IPA (n ¼ 17), SAIA (n ¼ 19), and CPA (n ¼ 15) subgroups, the median (IQR) BALF PTX3 levels in IPA were significantly higher than in SAIA or CPA (18.28 (7.21e13.51) ng/mL versus 6.97 (2.70e13. 19) ng/mL versus 3.60 (1.03e6.95) ng/mL, p <0.05; p <0.05) while the difference between SAIA and CPA was not significant (p 0.113) (Fig. 2b).…”
Section: Ptx3 Levels In Balfmentioning
confidence: 87%